Targeting the gut microbiome for type 2 diabetes management: a scoping review of systematic reviews and meta-analyses - Jiang, Rongsheng; Zheng, Likun; Fang, Jinxu; Guan, Qifan; Yuan, Hao; Liang, Jianfeng; Zhang, Jingwen; Han, Qingxuan; Liu, Mingjun (Frontiers in Endocrinology, 2026)
BackgroundThe Gut Microbiome (GM) is now a novel target for the treatment of Type 2 Diabetes Mellitus (T2DM), and several systematic reviews and Meta-analyses have provided evidence on the efficacy and safety of modulating GM in T2DM, but this evidence has not been consolidated.ObjectiveThe purpose of this scoping review was to summarize the currently available evidence and to assess the breadth and quality of these systematic reviews and Meta-analyses.MethodsThis study was guided by the PRISMA Extension for Scoping Reviews (PRISMA ScR) and the Arksey and O’Malley methodological framework. Electronic searches were conducted in multiple databases from the time of construction to May 1, 2025. Systematic reviews and Meta-analyses of regulatory GM to improve T2DM were included. 2 researchers independently screened full text, extracted review characteristics, and assessed methodological quality using the AMSTAR2 scale tool.ResultA total of 23 systematic reviews and Meta-analyses were included, which were published in 2015-2024.Probiotics/synbiotics were the most commonly used interventions; the included studies were generally of low methodological quality (only 1 was of high quality); most of the studies reported an improvement in some glycemic and lipid markers by modulating the microbiota, but there was heterogeneity in the results; and there was insufficient attention to adverse events.ConclusionThe available evidence suggests that regulating GM may be beneficial, but is limited by the quality of the studies, and future studies with large samples, long-term follow-up, and standardized adverse event reporting are needed to demonstrate its safety and long-term effectiveness conclusively.Systematic Review Registrationhttps://doi.org/10.17605/OSF.IO/PW28U.